Lack of association between the MDM2 promoter polymorphism SNP309 and clinical outcome in chronic lymphocytic leukimia - Kaderi, Mohd Arifin; Mansouri, Mahmoud; Zainuddin, Norafiza; Cahill, Nicola; Gunnarsson, Rebeqa; Jansson, Mattias; Kimby, Eva; Aleskog, Anna; Lundin, Jeanette; Glimelius, Bengt; Melbye, Mads; Juliusson, Gunnar; et al. (Elsevier, 2010)
The 309T>G polymorphism in the promoter region of the MDM2 gene, known as SNP309, has recently been suggested as an unfavorable prognostic marker in chronic lymphocytic leukemia (CLL) although this has been questioned. To investigate this further, we analyzed the MDM2 SNP309 genotypes in 418 CLL patients and correlated the results with established CLL prognostic factors, time to treatment and overall survival. In this Swedish cohort, no association existed between any particular MDM2 SNP309 genotype, overall survival and time to treatment. Furthermore, no correlation was shown between the MDM2 SNP309 genotypes and Binet stage, IGHV mutational status and recurrent genomic aberrations. In summary, this study argues against the use of the MDM2 SNP309 as a prognostic marker in CLL.